230k views
3 votes
3x - y = -1

-3x -y = 5

x = y =

1 Answer

3 votes

Answer:

Step-by-step explanation:

Step 1: Solve3x-y=-1 for y

3x-y=-1

3x-y+-3x=-1+-3x (add -3x to both sides)

-y=-3x-1

-y/-1=-3x-1/-1 (divide both sides by -1)

y=3x+1

Step 2: 3x+1 for y in -3x-y=5

-3x-y=5

-3x-(3x+1)=5

-6x-1=5 (simplify both sides of the equation)

-6x-1+1=5+1 (add 1 to both sides)

-6x=6

-6x/-6=6/-6 (divide both sides by -6)

x=-1

Step 4: Substitute -1 for x in y=3x+1

y=3x+1

y=(3)(-1)+1

y=-2

ANSWER: x=-1, and y=-2